Academic Senate Minutes 2006-05-11 - Academic Senate:::::::::
Chair Report. Agenda Approve. Minutes of 4/27/06 approved. APC resolution on the Academic Affair Strategic Plan approved. Faculty Consultation in University Decision Making amended and approved. Faculty Consultation in University Decision Making postponed to May 25th meeting. Tenure Track Hiring Policy approved. First Year Experience Pilot approved. Special Report: Vice President Katharyn Crabbe on the Campus Life reorganization. Resolution regarding Gender and Cultures Center approved. S&F by-laws change: Duties of the Past Chair first reading. Good of the Order.